Distinct histological alterations of cortical interneuron types in mouse models of Huntington’s disease - Voelkl, Kerstin; Schulz-Trieglaff, Elena Katharina; Klein, Rüdiger; Dudanova, Irina (Frontiers in Neuroscience, 2022)
Huntington’s disease (HD) is a debilitating hereditary motor disorder caused by an expansion of the CAG triplet repeat in the Huntingtin gene. HD causes neurodegeneration particularly in the basal ganglia and neocortex. In the cortex, glutamatergic pyramidal neurons are known to be severely affected by the disease, but the involvement of GABAergic interneurons remains unclear. Here, we use a combination of immunostaining and genetic tracing to investigate histological changes in three major cortical interneuron types – parvalbumin (PV), somatostatin (SST), and vasoactive intestinal peptide (VIP) interneurons – in the R6/2 and zQ175DN mouse models of HD. In R6/2 mice, we find a selective reduction in SST and VIP, but not PV-positive cells. However, genetic labeling reveals unchanged cell numbers for all the interneuron types, pointing to molecular marker loss in the absence of cell death. We also observe a reduction in cell body size for all three interneuron populations. Furthermore, we demonstrate progressive accumulation of mutant Huntingtin (mHTT) inclusion bodies in interneurons, which occurs faster in SST and VIP compared to PV cells. In contrast to the R6/2 model, heterozygous zQ175DN knock-in HD mice do not show any significant histological changes in cortical cell types at the age of 12 months, apart from the presence of mHTT inclusions, which are abundant in pyramidal neurons and rare in interneurons. Taken together, our findings point to differential molecular changes in cortical interneuron types of HD mice.